The Function of the Characters in the Kurdish Folklore Epic - lAlikhana Kofi - Taher, Nizar (Humanities Journal of University of Zakho, 2020)
The character is considered a prominent artistic element in the narrative text. The characters within the narrative text move and direct the events of the text forward. This study is an attempt to demonstrate the function of the characters in the epic narrative text in order to embody the meaning within the epic text.This study entitled (The Function of the Characters in the Kurdish Folklore Epic - lAlikhana Kofi) is divided into two parts. The first section was devoted to the theoretical aspect and we explored it in terms of the term personality And the concept, importance and types within the narrative text. As for the second section, it was devoted to the applied aspect, and we applied to the types of characters within the epic text, and in the last we concluded that there are three types of characters within the epic: the main, secondary and marginal. It also turns out that there are three main people inside the saga, and that there is a group of secondary people whose job is to assist the main characters within the saga, and there is also a group of marginal people who do not have any effective function within the epic events. On the course of events within the sag.